2018
DOI: 10.3892/ol.2018.9429
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide functions in stromal cell‑derived factor‑1‑induced cytoskeleton changes and the migration of Jurkat cells

Abstract: Stromal cell-derived factor-1 (SDF-1) regulates multiple cell signal pathways in a variety of cellular functions, including cell migration, proliferation, survival and angiogenesis. SDF-1-induced chemotaxis is an important step of lymphocyte migration. However, the molecular mechanisms that modulate SDF-1-mediated lymphocyte migration are not well identified. Nitric oxide (NO) has been found to function as a signaling molecule in a number of signaling pathways, including migration. In the present study, the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
2
1
0
Order By: Relevance
“…It is also possible that the SDF-1 CXCR4 axis is also involved in recruiting EPCs to sites of vascular injury. This theory is supported by the findings by Luo et al, 2018 [ 42 ]. They found that NO production was induced by SDF-1, which triggers multiple signalling pathways, resulting in chemokine-induced changes of the EPC cytoskeleton leading to enhanced cell migration [ 42 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It is also possible that the SDF-1 CXCR4 axis is also involved in recruiting EPCs to sites of vascular injury. This theory is supported by the findings by Luo et al, 2018 [ 42 ]. They found that NO production was induced by SDF-1, which triggers multiple signalling pathways, resulting in chemokine-induced changes of the EPC cytoskeleton leading to enhanced cell migration [ 42 ].…”
Section: Discussionsupporting
confidence: 81%
“…This theory is supported by the findings by Luo et al, 2018 [ 42 ]. They found that NO production was induced by SDF-1, which triggers multiple signalling pathways, resulting in chemokine-induced changes of the EPC cytoskeleton leading to enhanced cell migration [ 42 ]. The value of our models is that various doses/concentrations of different drugs, as well as combinations of drugs, can be tested faster than conventional models and also allows for real-time monitoring without measures such as anaesthesia being needed.…”
Section: Discussionsupporting
confidence: 81%
“…SDF-1α induces phosphorylation of WASP and FAK, along with a few other cytoskeletal proteins ( 146 ). SDF-1-induced cell migration has been attributed to reactive oxygen species (ROS) ( 143 ) and nitric oxide (NO) ( 147 ) signaling. SDF-1-induced actin filament rearrangement is abrogated by treating cells with ROS and NO synthase inhibitors, establishing the downstream role of ROS and NO in Jurkat cell migration.…”
Section: Regulation Of Immune Cell Migration Induced By Cancer Cellsmentioning
confidence: 99%